Ewastools: Infinium Human Methylation BeadChip pipeline for population epigenetics integrated into Galaxy. Issue 5 (13th May 2020) - Murat, Katarzyna; Grüning, Björn; Poterlowicz, Paulina Wiktoria; Westgate, Gillian; Tobin, Desmond J; Poterlowicz, Krzysztof
Abstract: Background: Infinium Human Methylation BeadChip is an array platform for complex evaluation of DNA methylation at an individual CpG locus in the human genome based on Illumina's bead technology and is one of the most common techniques used in epigenome-wide association studies. Finding associations between epigenetic variation and phenotype is a significant challenge in biomedical research. The newest version, HumanMethylationEPIC, quantifies the DNA methylation level of 850, 000 CpG sites, while the previous versions, HumanMethylation450 and HumanMethylation27, measured >450, 000 and 27, 000 loci, respectively. Although a number of bioinformatics tools have been developed to analyse this assay, they require some programming skills and experience in order to be usable. Results: We have developed a pipeline for the Galaxy platform for those without experience aimed at DNA methylation analysis using the Infinium Human Methylation BeadChip. Our tool is integrated into Galaxy (http://galaxyproject.org ), a web-based platform. This allows users to analyse data from the Infinium Human Methylation BeadChip in the easiest possible way. Conclusions: The pipeline provides a group of integrated analytical methods wrapped into an easy-to-use interface. Our tool is available from the Galaxy ToolShed, GitHub repository, and also as a Docker image. The aim of this project is to make Infinium Human Methylation BeadChip analysis more flexible and accessible to everyone.